Multicast service protection algorithm based on elastic optical network - Jingjing WU; Jianfang ZHANG (Tongxin xuebao)
With the rapid growth of the network traffic,the elastic optical network (EON) has been proposed as a promising solution due to its high spectrum efficiency and flexible bandwidth provision.Meanwhile,multicast routing and spectrum allocation,and the survivability of the network become more challenging than that in the conventional optical network.The routing for multicast traffic and its protection algorithm in EON was investigated.An integer linear programming (ILP) formulation with the objective to minimize total spectrum consumption was presented.In addition,a heuristic algorithm called multicast sub-tree protection algorithm (MSPA) to achieve sufficient protection and satisfy resources savings was designed.The simulation results demonstrate that comparing with the traditional multicast routing and protection algorithm,MSPA performs well in improving the blocking probability and the spectrum utilization of the network.